Identifying tannin Compounds in black Tea Extract Camellia Sinensis and the Effect of temperature on the amount of protein precipitant tannin - Ali Abd-Alameer, Maha (University of Thi-Qar Journal of Science, 2019)
This study aims at first identifying the kinds of tannins compounds in tea extract, second specifying the effect of temperature used in extracting tea on the amount of protein precipitant tannin. The amount of tannin has been estimated after being extracted from five pure types of cylanain , Indian, Indonesian tea and other than these ones. Then, it has been revealed that the higher the temperature the more amount of tannin is extracted in most of the extracts of tea. Tannins compounds have been identified in the five extracts ,by using the technique of "thin layer chromatography" (TLC) and the result was that the five extracts ; involve ;Tannic acid, Gallic acid and Ellagic acid; in addition to more four compounds with equal values of relative flow ,these compounds might be Epicatchin (EC), Epigallocatchin(EGC),Epicatchin gallate(ECG) and Epigallocatchin gallate(EGCG).